1988
DOI: 10.1038/335509a0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct dental development patterns in early fossil hominids

Abstract: New studies on the jaws of hominids, based on incremental growth markings in teeth, can now provide an absolute timescale with which to calibrate dental developmental events such as tooth emergence. These new estimates of crown-formation times and the observed sequences of dental development are different in the hominids Australopithecus and Paranthropus. Early hominids evidently had shorter periods of dental development than modern humans and therefore a less prolonged infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
2
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(153 citation statements)
references
References 34 publications
10
136
2
3
Order By: Relevance
“…Australopithecus and differs from the condition in Old World monkeys, Paranthropus, and Homo (Beynon and Dean, 1988;Swindler and Meekins, 1991;Dirks, 1998Dirks, , 2003Dean and Reid, 2001;Dirks et al, 2002 (2004)]. Kelley (1997) cited M1 emergence times in various macaque species as being between 16 and 18 months, but only 9.9 months in the much smaller Cercopithecus aethiops.…”
Section: Crown Formation Timesmentioning
confidence: 99%
“…Australopithecus and differs from the condition in Old World monkeys, Paranthropus, and Homo (Beynon and Dean, 1988;Swindler and Meekins, 1991;Dirks, 1998Dirks, , 2003Dean and Reid, 2001;Dirks et al, 2002 (2004)]. Kelley (1997) cited M1 emergence times in various macaque species as being between 16 and 18 months, but only 9.9 months in the much smaller Cercopithecus aethiops.…”
Section: Crown Formation Timesmentioning
confidence: 99%
“…These long-period striae manifest as enamel ridges, called perikymata, at the crown surface. Importantly, multiplying the total number of perikymata by the number of short-period cross-striations between them gives a very accurate estimate of the number of days over which a tooth crown formed, and hence, the age of an immature specimen (Dean, 1987;Beynon and Dean, 1988;Risnes, 1998). Of course, periodicity data can only be used to age individuals in whom dental development is not yet complete.…”
Section: Figmentioning
confidence: 99%
“…Bromage and Dean (1985) reassessed the age at death of fossil hominids using incremental features, and concluded that early humans were characterized by ape-like dental development, in contrast to the previously assumed modern human pattern. These were followed by many more studies of fossil hominids that examined the nature of enamel development and enamel thickness as revealed by microstructure (Beynon and Wood, 1986;Dean et al, 1986;Beynon and Dean, 1987;Beynon and Wood, 1987;Dean, 1987a,b;Beynon and Dean, 1988;Grine and Martin, 1988;Mann et al, 1991;Beynon, 1992;Dean et al, 1993a;Ramirez Rozzi, 1993a,b;Mann et al, 1994;Ramirez Rozzi, 1994;Dean, 1995;Ramirez Rozzi, 1997;Ramirez Rozzi et al, 1997;Ramirez Rozzi, 1998;). These investigations have provided information on age at death in individuals with developing dentitions, the absolute and relative timing of dental development, differences in the developmental pathways of enamel formation, and life history characteristics.…”
Section: Introductionmentioning
confidence: 99%